Mitigating secondary salinization in grapes: long-term benefits of biochar and cow dung - Zhou, Hongyin; Yu, Zhong; Zhang, Shiying; Zong, Qinghou; Zhang, Yulian; Pang, Yuhan; Zhang, Naiming; Yue, Xianrong; Deng, Yishu; Xia, Yunsheng (Frontiers in Plant Science, 2025)
Secondary salinization of soil seriously hinders the healthy cultivation of facility grapes. Biochar has been shown to mitigate the negative effects of saline stress on plants. However, the long-term response mechanism between the soil’s key physicochemical properties, ion concentration, and enzyme activity and the physiological resistance of facility grape plants to biochar combined with cow dung application to alleviate the soil secondary salinization stress remains unclear. In this study, a field experiment was set up once in September 2021 with five different treatments, including no amendments. which was used as the blank control (CK), and application of biochar (10 t·ha-1, T1), cow dung (30 t·ha-1, T2), biochar mixed with cow dung (5 t·ha-1+15 t·ha-1, T3), and biochar mixed with cow dung (10 t·ha-1+30 t·ha-1, T4), respectively. The results showed that compared with the CK treatment, application treatments significantly reduced soil total salt(TS) content and the electrical conductivity(EC) value; increased soil water-stable aggregates and nutrient content; stimulated an increase in soil urease (S-UE), sucrose (S-SC) and phosphatase(S-ALP)activities; and changed soil exchangeable calcium and magnesium ion concentrations. Among the treatments, the T4 treatment reduced TS and EC by 73.03% and 61.11%, respectively. Biochar combined with cow dung significantly increased chlorophyll content and reduced malondialdehyde content (MDA), the activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) in grape leaves. The T4 treatment decreased MDA, SOD, POD, and CAT by 54.59%, 40.14%, 44.28%, and 70.17% compared with the CK treatment, respectively. Correlation analysis showed that the balance of soil exchangeable calcium and magnesium ions and the stability of soil aggregate structure were the key factors in alleviating soil secondary salinization stress. In conclusion, biochar combined with cow dung application can alleviate the oxidative stress response of grape plants and improve the quality of grapes by improving the structure of soil water-stable aggregates, coordinating the concentration of soil exchangeable calcium and magnesium ions, and stimulating soil enzyme activity.